Miscibility and Solubility of Caffeine and Theophylline in Hydroxypropyl Methylcellulose - Edyta Leyk; Marek Wesolowski (MDPI AG, 2021)
As amorphization may improve the solubility and bioavailability of a drug substance, the aim of this work was to assess to what extent the crystallinity of caffeine (CAF) and theophylline (TF) can be reduced by homogenization with a polymeric excipient. To realize this purpose, the physical mixtures of both methylxanthines with hydroxypropyl methylcellulose (HPMC) were examined using differential scanning calorimetry (DSC), hot-stage microscopy (HSM), Fourier-transform infrared (FTIR) and Raman spectroscopy. Moreover, phase diagrams for the physical mixtures were calculated using theoretical data. Results of DSC experiments suggested that both CAF and TF underwent amorphization, which indicated proportional loss of crystallinity for methylxanthines in the mixtures with HPMC. Additionally, HSM revealed that no other crystalline or amorphous phases were created other than those observed for CAF and TF. FTIR and Raman spectra displayed all the bands characteristic for methylxanthines in mixtures with HPMC, thereby excluding changes in their chemical structures. However, changes to the intensity of the bands created by hydrogen bonds imply the formation of hydrogen bonding in the carbonyl group of methylxanthines and the methyl polymer group. This is consistent with data obtained using principal component analysis. The findings of these studies revealed the quantities of methylxanthines which may be dissolved in the polymer at a given temperature and the composition at which methylxanthines and polymer are sufficiently miscible to form a solid solution.